AN APPRAISAL OF THE IMPACT OF ISLAMIC CO-OPERATIVE SOCIETIES ON SOCIO-ECONOMIC DEVELOPMENT IN SOME SELECTED STATES IN NIGERIA - Olayinka, Aminu Abdulrahim; Ganiy, Abdul Fattah Abdul; Sirajo, Murtala (International Journal of Islamic Business & Management, 2021)
This study assessed the impact of Islamic Co-operatives Societies (ICSs) theoretically, legally and practically on Socio-Economic Development in Nigeria and consider its establishment in our various conventional interest-based economy community, which contradicts the ideals of Islamic principles of finance. The research was carried out within the general framework of Islamic financial principles and precepts. The research work focused on the needs of financing a large and growing Muslims community in line with their Islamic tenets thereby concentrating on the feasibility of adopting suitable ICS’s modus operandi for the Muslim Community. It also studies the current realities of the ICSs being practiced in Nigeria from the perspective of the theories of Islamic financial system. Within this spectrum the operations and functions of registered Islamic cooperative societies in Adamawa Gombe, Kwara, and Zamfara States were reviewed. The study examined the key role of ICSs in an economy in fulfilling the microfinance needs of Muslims community, and find out that ICSs is a viable alternative solution to the conventional cooperative models and also alternative measure with potentiality to alleviate poverty. The study is limited in scope in a sense that it is not a comparative study of Islamic financial system with doctrines of other religions, ideologies and systems. JEL Classification Codes: D6, F63, R51, Q01, P13.